2000
DOI: 10.1093/clinchem/46.5.650
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponins I and T Are Biological Markers of Left Ventricular Dysfunction in Septic Shock

Abstract: Background: Cardiac depression in severe sepsis and septic shock is characterized by left ventricular (LV) failure. To date, it is unclear whether clinically unrecognized myocardial cell injury accompanies, causes, or results from this decreased cardiac performance. We therefore studied the relationship between cardiac troponin I (cTnI) and T (cTnT) and LV dysfunction in early septic shock. Methods: Forty-six patients were consecutively enrolled, fluid-resuscitated, and treated with catecholamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
145
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(164 citation statements)
references
References 38 publications
10
145
1
8
Order By: Relevance
“…However, most studies reporting the use of troponin in sepsis patients had a sample size of fewer than 50 patients. 11,14,[16][17][18]…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies reporting the use of troponin in sepsis patients had a sample size of fewer than 50 patients. 11,14,[16][17][18]…”
Section: Limitationsmentioning
confidence: 99%
“…9 The prognostic effects of elevated troponins in patients with sepsis have been studied by several investigators. [10][11][12][13][14][15] Some investigators found troponin to be an independent predictor, and others found troponin to be elevated in patients with sepsis but did not independently predict mortality. This variation in the published results might be resulting from the differences in the assays used to quantify troponin and the variability in the cut-off levels to define 'elevated' troponin in the published results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,90 While the exact mechanisms are unknown, cardiac oxygen demand exceeding supply, septic microemboli, toxic effects from bacterial endotoxins, and cardiac depressant effects from cytokines such as tumor necrosis factor-a are postulated mechanisms. 74,91 Ischemia and reperfusion injury secondary to microvascular dysfunction may also be involved. In humans, elevated cTn values during sepsis are associated with left ventricular dysfunction.…”
Section: Infection and Inflammationmentioning
confidence: 99%
“…In humans, measurement of serum cardiac troponin concentration is most commonly used in the diagnosis of myocardial infarction secondary to coronary heart disease. [4][5][6] However, other causes of myocardial injury more commonly encountered in veterinary medicine, such as myocardial trauma, 7,8 myocarditis, 9,10 advanced congestive heart failure, 11,12 sepsis, 13,14 and anthracycline chemotherapy, [15][16][17][18] also cause increases in circulating cardiac troponin in humans. Several recent experimental studies also have identified increases in cTnT as a specific marker of myocardial damage secondary to myocardial infarction in dogs 2,19 and doxorubicin cardiotoxicosis in rats and mice.…”
mentioning
confidence: 99%